Maternal Mortality a Multifactorial Public Health Problem - Hospital Belén de Trujillo (Risk factor's) (SCIÉNDO INGENIUM, 2021)
The present study aims to determine the factors significantly associated with maternal mortality, it is a retrospective observational study, of cases and controls, two groups were formed: Case Group (63): pregnant women who leave the hospital alive, registered in the General Office of Epidemiology of the Hospital and in the Perinatal Computer System 2000 (SIP 2000), and Control Group (315): pregnant women who leave the hospital alive, registered in the Perinatal Computer System 2000 (SIP 2000). The chi-square test was used in the bivariate analysis and the OR and its 95% CI were used as a statistician. It is concluded that the most significant factors among the socioeconomic factors: The non-origin of the Trujillo district (OR = 2.04), Studies until primary (OR = 6.82), Distance to the hospital greater than 10 km (OR = 4.47) and time elapsed until reaching the major hospital 10 minutes (OR = 2.22); Among the gyneco-obstetric factors significant to explain maternal mortality we find: extreme age (OR = 2.43), Multiparity (OR = 4.19), Non-term delivery (OR = 4.26), lack of prenatal control ( OR = 5.4), similarly, Preeclampsia / Eclampsia (OR = 5.76), and Placenta previa (OR = 10.61).
Keywords: Maternal death; multifactorial problem; risk factors